2014
DOI: 10.4103/0970-9185.142843
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of obstetric patient′s outcome in intensive care unit of a tertiary care center

Abstract: Background and Aims:Admission to an intensive care unit (ICU) is considered as an objective marker of severe maternal morbidity. The aim was to assess the incidence and possible risk factors of obstetric patient admissions in the multidisciplinary ICU of a tertiary care center with emphasis on standardized mortality ratio (SMR).Material and Methods:A retrospective five year ICU record analysis was done for all pregnant women, who were admitted to multidisciplinary ICU of a tertiary care hospital during June 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 19 publications
(37 reference statements)
2
23
1
Order By: Relevance
“…The mean age and the age distribution of the critically ill obstetric patients in the present study correlate with other contemporary Indian studies,[172021222324] but studies from abroad report a higher maternal age. [11131415] Although advanced maternal age has not been shown to be uniformly associated with CCU admissions and a median age of 30 years is consistent with birth age patterns in developed countries,[27] the noteworthy point in Indian studies is the need of critical care in the patients well under thirty.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The mean age and the age distribution of the critically ill obstetric patients in the present study correlate with other contemporary Indian studies,[172021222324] but studies from abroad report a higher maternal age. [11131415] Although advanced maternal age has not been shown to be uniformly associated with CCU admissions and a median age of 30 years is consistent with birth age patterns in developed countries,[27] the noteworthy point in Indian studies is the need of critical care in the patients well under thirty.…”
Section: Discussionsupporting
confidence: 90%
“…[18192324] The median duration (in days) of ventilation of 2 (IQR 1-7) in our study closely correlates most Indian studies. [172122] The high central venous catherization rate (84.88%) in our study, although similar to an Indian study headed by Bhadade et al (82.8%),[18] is much higher than that in studies from abroad. [11121315] This high rate was mainly for taking advantage of multiple venous accesses for unstable patients.…”
Section: Discussionsupporting
confidence: 85%
“…In a systematic review of the literature during 1990-2008, the hypertensive syndrome was found to be the most prevalent in a specific obstetric cause for hospitalization (5,14) Hypertensive gestational syndromes including chronic hypertension and the entire spectrum of preeclampsia, complicated about 7% of the pregnancies. Moreover, deaths related to this clinical condition have been constantly reported, often ranging from 1 to 24% (15). In the current study, mortality rate (44.4%) was higher than that of expected in the available literature.…”
Section: Discussioncontrasting
confidence: 58%
“…There are some predisposing factors for sepsis in pregnancy such as CS, lack of prenatal care, abortion induction, premature rupture of the placental membrane, and conditions inherent to the obstetric population (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Admission to an ICU is measured as an indicator of severe morbidity. [ 10 ] Thereafter, the current study was designed to review the data retrieved from the archive on the deaths in ICU. It was carried out by analyzing the fatal case documents of deaths occurred during 2-year duration in a 9-bedded ICU to investigate mainly the mortality rate among the critically ill patients.…”
Section: Introductionmentioning
confidence: 99%